Gastroprotective Activities of Aqueous and 80% Methanol Leaf Extracts of Stephania abyssinica (Quart.-Dill. and A. Rich.) Walp. (Menispermaceae) in Rats - Firehun B; Nedi T (Dove Medical Press, 2023)
Banchayehu Firehun,1,2 Teshome Nedi2 1School of Pharmacy, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Teshome Nedi, Email teshome.nedi@aau.edu.etBackground: An ethnobotanical study showed that the leaf of Stephania abyssinica (S. abyssinica) is used for the treatment of gastritis, but there is no scientific investigation.Objective: The aim of this study was to evaluate the gastroprotective activities of both aqueous and 80% methanol leaf extracts of S. abyssinica in experimental rats.Methods: Decoction and maceration techniques were used to prepare aqueous and 80% methanol leaf extracts, respectively. The extracts were evaluated against pyloric ligation, indomethacin, and ethanol-induced gastric ulcer models at doses of 100, 200, and 400 mg/kg. Negative control received 2% tween 80, while positive controls received 20 mg/kg of omeprazole and 100 μg/kg of misoprostol. Parameters, such as ulcer index, gastric mucin content, gastric juice volume, pH, and free and total acidity were measured.Results: In the pyloric ligation induced gastric ulcer model, all doses of both extracts significantly reduced the ulcer index and gastric juice volume, while doses of 200 and 400 mg/kg exhibited a significant increment in mucus content and gastric juice pH as well as decrease in free and total acidity as compared to negative control. In indomethacin and ethanol induced gastric ulcer models, pretreatment with both extracts significantly reduced the ulcer index and enhanced gastric mucin content in a dose-dependent manner. Phytochemical screening of both extracts showed the existence of flavonoids, phenols, tannins, saponins, alkaloids, and coumarins with high contents of phenols, flavonoids, and alkaloids in 80% methanol extract.Conclusion: This study revealed that aqueous and 80% methanol leaf extracts of S. abyssinica possessed remarkable gastroprotective activities against experimentally induced gastric ulcer models, and this possibly justify the traditional use of S. abyssinica leaves to treat gastritis.Keywords: gastroprotective, Stephania abyssinica, pylorus ligation, indomethacin, ethanol